Effect of Cutaneous Feedback on the Perceived Hardness of a Virtual Object - Park, Jaeyoung; Oh, Yonghwan; Tan, Hong Z. (IEEE COMPUTER SOC, 2018)
We investigate the effect of adding cutaneous cues to kinesthetic feedback on the perception of a virtual object's hardness. A cutaneous haptic interface is designed to deliver hardness information to a user's fingertip along with a force-feedback interface, and the corresponding rendering strategy is implemented. Two sets of experiments are conducted to evaluate the proposed approach for hardness perception using one-finger touch and two-finger grasp. Experimental results indicate that the addition of cutaneous feedback can make the virtual surface feel significantly harder than the nominal stiffness delivered by force-feedback alone. In addition, the perceived hardness is significantly affected by the rate of hardness rendered with a cutaneous interface for the nominal stiffness K = 0.3 and 0.5 N/mm. For two-finger grip, the effect of a virtual object's thickness has a significant effect on the perceived hardness measured in stiffness. When the perceived hardness is converted to Young's modulus, the effect of thickness is insignificant.
Keywords: HAPTIC PERCEPTION; SENSORY SUBSTITUTION; DISCRIMINATION; FORCE; TELEOPERATION; AUGMENTATION; INFORMATION; SOFTNESS; CONTACT; DESIGN